(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to study the impact of financial reporting on financial services technology on the value of private Iraqi banks, by applying it to twenty-three private Iraqi banks listed on the Iraq Stock Exchange for the period from 2018 to 2023, with (134) observations. The research variables were measured based on the published financial reports of private Iraqi banks by conducting approved statistical tests such as conducting statistical analysis based on the multiple linear regression model using the statistical analysis program (SPSS). Among the most important findings of the researchers is that financial reporting on financial services technology affects the value of banks at a significance level of 5%, with the stability of other independent variables represented by the debt ratio, return on assets, and bank size. The researchers also found that financial reporting on financial services technology provides detailed information for each category of intangible assets, specifically software and electronic systems included in the supplementary explanations to the financial statements, ease of understanding and interpreting financial information, and the possibility of comparison to determine future growth rates. Based on what they have reached above, the researchers recommend that Iraqi private banks increase investment in software and electronic systems to keep pace with the extent of development in the field of providing financial services and benefit from the experiences of leading banks in this field or build partnerships with private financial institutions to develop financial solutions dedicated to supporting the innovation system for banks to ensure survival and growth in a competitive business environment. The researchers also recommend the necessity of increasing financial reporting on financial services technology by including financial indicators such as technological revenues divided by technological assets in their annual reports to increase understanding and interpretation of the importance of technologies and software used in banking activities through the growth of financial returns.